The psychophysiological regulation of pacing behaviour and performance during prolonged endurance exercise - Venhorst Andreas (Department of Human Biology, 2018)
Current models of exercise regulation almost solely rely on the Gestalt phenomenon of perceived exertion. This limits a more comprehensive understanding of how causeeffect relationships come to be and how perception-action coupling determines pacing behaviour and performance fatigability. A three-dimensional framework of centrally regulated and goal-directed exercise behaviour is proposed, which differentiates between sensory-discriminatory, affectivemotivational, and cognitive-evaluative processes hypothesised to underpin perceived fatigability. In short: (A) perceived physical strain and perceived mental strain are primary regulators of pacing behaviour necessary to align planned behaviour with current physiological state, (B) core affect plays a primary and mediatory role in performance regulation, and (C) the mindset- shift associated with an action crisis plays a primary role in volitional self-regulatory control and decision-making. In study one, 23 cyclists of distinct performance levels engaged in 70-km individual and head-to-head competition time trials against a performance matched opponent. Sensory constructs were primarily associated with regulation of pacing behaviour. Affective and cognitive constructs acted as context-dependent modifiers and were primarily associated with regulation of performance. A five-step structural equation modelling procedure was applied to assess the extent to which the observed data fit the hypothesised cause–effect relationships under the constraint of psychological duress: valence deterioration was found to mediate the relationship between falling-behind and action crisis; which in turn predicted increased non-adaptive endocrinological distress response; which in turn predicted performance decrement. In study two, 22 highly-trained runners completed two self-paced 20-km treadmill time trials in a tapered condition and with locomotor muscle fatigue and exercise-induced muscle damage. The latter was associated with medium increases in markers of physiological distress and large alterations in perceived physical strain, affective valence, and cognitive mindset. This indicates heuristic and rational antecedents in the goal-disengagement process. Structural equation modelling confirmed the hypothesised dual-pathway model under the constraint of physical duress: haematological indicators of EIMD predicted (1) amplified physiological strain and non-adaptive endocrinological distress response and (2) increase in perceived physical strain, which mediated and predicted decrease in valence; which in turn predicted an increase in action crisis; and both physiological and perceptual effects predicted performance fatigability. The proposed framework has the potential to enrich theory development in centrally regulated and goal-directed exercise behaviour by providing novel insights into and more complete account of the dynamic and complex processes in strain-perceptionthinking-action coupling during prolonged endurance exercise.